PSIQUE (CIPEEX, 2024)
THE OBJECTIVE OF THE PSIQUE PROJECT IS TO DEVELOP A MOBILE APP FOR ANDROID AND IOS FOR PSYCHOLOGICAL AND PSYCHIATRIC CARE, SCHEDULING THERAPEUTIC SESSIONS AND MEDICAL APPOINTMENTS, AS WELL AS MAKING VIDEO CALLS BETWEEN HEALTHCARE PROFESSIONALS AND PATIENTS.THE APP ALSO PROVIDES ANALYSIS BASED ON THE DASS-21 (DEPRESSION ANXIETY AND STRESS SCALE) WHICH ALLOWS THE PATIENT TO MONITOR THEIR LEVELS OF DEPRESSION, ANXIETY AND STRESS, AS WELL AS THEIR EVOLUTION THROUGHOUT THE ANALYSES. THE DASS-21 QUESTIONNAIRE HAS 21 QUESTIONS THAT MUST BE ANSWERED BY THE PATIENT BEFORE THE FIRST APPOINTMENTANOTHER FEATURE TO BE HIGHLIGHTED BY THE APP IS THE EMOTIONAL DIARY METHODOLOGY THAT PROVIDES EMOJIS THAT REPRESENT EMOTIONAL STATES AND QUESTIONS ABOUT WHAT WAS GOOD IN THE PATIENT'S DAY AND WHAT WAS BAD IN ORDER TO HELP THEM IDENTIFY POSSIBLE STRESSORS.ANOTHER OBJECTIVE OF THE PROJECT IS TO DEVELOP A SERVICE PLATFORM, WHICH IN ADDITION TO THE RESOURCES ALREADY MENTIONED, ALSO OFFERS A COMFORTABLE AND SIMPLIFIED USER EXPERIENCE TO PATIENTS, ESPECIALLY THOSE WHO ARE EMOTIONALLY FRAGILE.THE RESOURCES OF AN MVP (MINIMUM VIABLE PRODUCT) ARE THE SERVICE SEARCH, SESSION SCHEDULING, SERVICE HISTORY AND EMOTIONAL DIARY FUNCTIONALITIES.FOR THE DEVELOPMENT OF THE APP, THE DEVELOPMENT FRAMEWORK SELECTED IS REACT NATIVE, AS IT ALLOWS THE SAME CODE TO COMPILE THE APP FOR BOTH ANDROID AND IOS. NODE JS EXPRESS TO CREATE THE SERVER API THAT WILL MANAGE THE DATABASE IN THE MVC (MODEL VIEW CONTROLLER) ARCHITECTURE.